(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article studies the purpose of the utilization fee collection system, its various applications, and how it differs from similar mechanisms. It provides a comparative analysis of international and domestic experiences in its implementation. The article also examines practical challenges in the field and offers realistic suggestions for resolving them. In addition, it touches upon the impact of utilization fees on the global economy and the types of products for which the fees are levied. The current conditions are detailed, and the article presents topic-based scientific proposals and practical recommendations.